Felicity the Friday fairy - Meadows, Daisy (New York : Scholastic, 2006)
Kirsty and Rachel agree to help when Jack Frost steals Felicity the Friday Fairy's Fun Day Flag, turning a day of cookie baking into a chore.
Rainbow magic: The fun day fairies ;v05.
Rainbow magic ;v40.
"Previously published as Freya the Friday Fairy by Orchard U.K. in 2006"--Page facing title page.
Keywords: Days -- Juvenile fiction; Magic -- Juvenile fiction; Cookies -- Juvenile fiction; Baking -- Juvenile fiction; Lost articles -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Goblins -- Juvenile fiction; Fantasy fiction, Juvenile